Solow meets market socialism: regional convergence of output per worker in China - Erich Gundlach (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
Regional output per worker has converged in China in the era of market socialism since 1978. The estimated speed of convergence is about 2 percent. This speed of convergence can be explained by an open economy neoclassical growth model in the tradition of Robert Solow. My empirical results show that capital mobility has been high across Chinese provinces and that the production elasticity of human capital is about twice as high as the production elasticity of physical capital. With less interprovincial capital flows as the result of an expected increase in fiscal decentralization, the speed of convergence of regional output per worker is likely to decline.
Keywords: O21; 330; Regionales Wachstum; Entwicklungskonvergenz; Arbeitsproduktivität; Wachstumstheorie; Humankapital; China